The Renfrew Unified Treatment for Eating Disorders and Comorbidity: Long-Term Effects of an Evidence-Based Practice Implementation in Residential Treatment - Thompson-Brenner, Heather; Singh, Simar; Gardner, Taylor; Brooks, Gayle E.; Smith, Melanie T.; Lowe, Michael R.; Boswell, James F. (Frontiers in Psychiatry, 2021)
BACKGROUND: The Renfrew Unified Treatment for Eating Disorders and Comorbidity (UT) is a transdiagnostic, emotion-focused treatment adapted for use in residential group treatment. This study examined the effect of UT implementation across five years of treatment delivery. METHODS: Data were collected by questionnaire at admission, discharge (DC), and 6-month follow-up (6MFU). Patient outcomes were measured by the Eating Disorder Examination-Questionnaire, the Center for Epidemiologic Studies-Depression Scale, the Brief Experiential Avoidance Questionnaire (BEAQ), the Anxiety Sensitivity Index, and the Southampton Mindfulness Scale. Data were analyzed for N=345 patients treated with treatment-as-usual (TAU), and N=2,763 treated with the UT in subsequent years. RESULTS: Results from multilevel models demonstrated a significant interaction between implementation status (TAU vs. UT) and time, both linear and quadratic, for the depression, anxiety sensitivity, experiential avoidance, and mindfulness variables. This suggests that patients treated with the UT showed more improvement in these variables on average, as well as more rebound between DC and 6MFU. Results from multilevel models examining eating disorder outcome showed no significant difference between the TAU and UT for the full sample, but a significant three-way interaction indicated that the UT produced more improvement in the EDE-Q relative to the TAU particularly for patients who entered treatment with high levels of experiential avoidance (BEAQ score). CONCLUSION: This long-term study of a transdiagnostic, evidence-based treatment in residential care for eating disorders and comorbidity suggests implementation was associated with beneficial effects on eating disorder, depression, and emotion function outcomes, sustained over multiple years.